Isolation and Characterization of Cellulose Microfibril (MFC) from Gracilaria sp. with Different Quality Grades - Nurhayati; Irianto, Hari Eko; Supriyanto, Agus; Kusumawati, Rinta; Basmal, Jamal; Munifah, Ifah; Setiawati, Natalia Prodiana; Kusumaningrum, Wida Banar; Amanda, Putri; Roziafanto, Ahmad Nandang; Riastuti, Rini; Chalid, Muchamad (Science and Technology Indonesia, 2025)
The cellulose found in Gracilaria sp. has not been utilized optimally. This study investigated the characteristics of cellulose and cellulose microfibril (MFC) isolated from three grades of Gracilaria sp. Descriptive tests were performed to determine the quality of eachgrade, including observations on moisture content, ashcontent, CAW,andimpurities. The extraction process involved separating agar from Gracilaria sp., isolating cellulose using 10% NaOH, and bleaching cellulose with 3% NaOCl. The bleached cellulose was then ultrasonicated to produce MFC. Characterization was performed using FTIR, XRD, PSA, STA, DSC, and py-GC/MS. FTIR analysis indicated similar peaks for both cellulose forms but only differed in transmittance intensity. The crystallinity index from XRD analysis was 22–39% for raw Gracilaria sp., 25–46% for cellulose, and 68–89% for MFC. The particle size distribution of MFC mostly ranged between 200–500 nm, with 63.16% frequency. TG analysis showed cellulose decomposition with a Tonset of 231–260oC and a Tmax of 318–326oC. DSC analysis revealed that sonication enhances the polymer structure’s crystallization compared to pre-sonicated cellulose and raw material. The py-GC/MS analysis showed that D-allose and n-Hexadecanoic acid were the major components.